Transformational Changes Psychology of an Integrated Identity - Sergeyeva, Alla (Psychological Prospects Journal, 2016)
The article presents the results of theoretical and empirical analysis of psychological factors integral transformation of personal identity. The content of the psychological phenomenon of integrated identity has been clarified, the key conceptual approaches to the study of integral identity have been analyzed, explication and description of internal and external factors of the formation of identity is held, the current trends in the study of personality factors of transformational change of identity (especially the self, personal willingness to change, and changes in their life) have been highlighted. As a result of empirical studies the presence of ambiguous correlations between performance and integrated features of the self-identity has been revealed. Most indicators of the integral identity (easy to change its identity, the activity of its construction, the breadth of the search of their identity, status identity in religious, ethnic and gender spheres of social relations), demonstrate a significant correlation with the features of the self (self-esteem, the expectation of a positive attitude from others, self-acceptance).Keywords: integral identity, structural components of an integrated identity, psychological factors (especially the self-esteem and personal willingness to change).